Direct oral anticoagulation and mortality in moderate to high-risk atrial fibrillation. Issue 19 (10th April 2019) - Arbel, Ronen; Sergienko, Ruslan; Hammerman, Ariel; Dotan-Greenberg, Sari; Batat, Erez; Avnery, Orly; Greenberg, Dan; Ellis, Martin H
Abstract : Objective: Although direct oral anticoagulants (DOAC) are the recommended antithrombotic therapy for patients with non-valvular atrial fibrillation (NVAF), anticoagulation in patients with NVAF is still inadequate. The effect of withholding DOAC therapy on patient survival is unknown. Therefore, our objective was to compare all-cause mortality rates between DOAC-treated patients with NVAF and similar patients receiving no anticoagulation. Methods: We performed a retrospective cohort study analysing Clalit Health Services' extensive electronic database, regarding all newly diagnosed, anticoagulant-naïve patients with NVAF who were eligible for DOAC therapy from 1 January 2011 to 31 December 2016. Patients who received DOAC therapy were matched by propensity scoring to patients receiving no anticoagulation. The primary outcome was all-cause mortality. Final patient follow-up date was 15 May 2017. Results: 18 901 eligible patients were identified. 8298 received treatment with a DOAC and 10 603 received no anticoagulation therapy. Of those, 5657 patients who received DOAC therapy were matched with 5657 patients who did not receive any anticoagulant. Death occurred in 715 patients in the DOAC-treated group (7.6% per year) and in 2075 patients in the non-anticoagulated patient group (11.1% per year). DOAC therapy was associated with significantly lower risk for all-cause mortality (HR=0.69, 95% CI 0.63 to 0.75, p<0.001). The benefit of DOAC therapy was demonstrated across all subgroups analysed. Conclusions: In this cohort of newly diagnosed patients with NVAF, DOAC therapy was associated with a significantly lower risk of death compared with no oral anticoagulation. Our findings provide further evidence for the importance of providing DOAC anticoagulation in patients with NVAF.